Exploration of Adolescent Health Services and Utilization in Mamuju District, West Sulawesi - Nurbaya, Nurbaya; Najdah, Najdah; Irwan, Zaki; Yudianti, Yudianti; Nurliah, Nurliah; Rasmaniar, Rasmaniar; Nurlaela, Euis (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Eating habits and nutritional status among adolescents in Mamuju, West Sulawesi, showed that adolescents with unhealthy eating habits tend to have a higher incidence of overweight and obesity compared to those with healthy eating habits. This underscores the need for early nutrition education for adolescents. This study aimed to explore the types of health and nutrition services received by adolescents at primary healthcare services in Mamuju District, West Sulawesi.Methods: An explanatory sequential mixed-methods design was used, combining cross-sectional and qualitative methods. The study involved 305 high school adolescents in Mamuju, selected through random sampling. Quantitative data were collected via surveys using structured questionnaires. Qualitative data were obtained from in-depth interviews with 8 key informants (health workers, teachers, and students) and focus group discussions (FGDs) with 8-10 participants per session, who were selected through purposive sampling to ensure diverse perspectives.Results: The results showed that the majority of adolescents accessed healthcare services through the Puskesmas (99.3%), as its easy access reported by 92.2% respondents. However, most respondents (77.7%) were unaware of the types of healthcare services available at the Puskesmas. The most commonly received services were mental health counseling (9.9%) and nutrition education (5.9%).Conclusion: These findings indicate the need for greater dissemination of information about available healthcare services through social media, as well as the strengthening of health and nutrition education programs for adolescents to support healthy lifestyles